2014
DOI: 10.1002/ange.201403458
|View full text |Cite
|
Sign up to set email alerts
|

Highly Ordered and Highly Aligned Two‐Dimensional Binary Superlattice of a SWNT/Cylindrical‐Micellar System

Abstract: We report a highly ordered intercalated hexagonal binary superlattice of hydrophilically functionalized singlewalled carbon nanotubes (p-SWNTs) and surfactant (C 12 E 5 ) cylindrical micelles. When p-SWNTs (with a diameter slightly larger than that of the C 12 E 5 cylinders) were added to the hexagonally packed C 12 E 5 cylindrical-micellar system, p-SWNTs positioned themselves in such a way that the freevolume entropies for both p-SWNTs and C 12 E 5 cylinders were maximized, thus resulting in the intercalated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 68 publications
0
2
0
Order By: Relevance
“…The peak ratios of and can be indexed to the FCC nanostructure by the Bragg peak index ( Figure 2 a) [ 28 , 29 , 30 ]. Although the sample phases of the P105-5mS complex were visually unchanged, the SAXS signal patterns slowly changed from the FCC nanostructure to the hexagonal phase (peak ratio of ) with an increase in the temperature above 50 °C (light blue arrow in Figure 2 b,c) [ 28 , 31 , 32 ]. The SAXS measurements showed that the interesting phase behavior in the nanoscale region differed from a visual inspection, which revealed only a solid-like gel.…”
Section: Resultsmentioning
confidence: 99%
“…The peak ratios of and can be indexed to the FCC nanostructure by the Bragg peak index ( Figure 2 a) [ 28 , 29 , 30 ]. Although the sample phases of the P105-5mS complex were visually unchanged, the SAXS signal patterns slowly changed from the FCC nanostructure to the hexagonal phase (peak ratio of ) with an increase in the temperature above 50 °C (light blue arrow in Figure 2 b,c) [ 28 , 31 , 32 ]. The SAXS measurements showed that the interesting phase behavior in the nanoscale region differed from a visual inspection, which revealed only a solid-like gel.…”
Section: Resultsmentioning
confidence: 99%
“…For example, the local signature of yielding during large amplitude oscillatory shear has been detected in concentrated oil-in-water nanoemulsions [120]. The shear flow is also an elegant method to orient the sample and deduce high resolution structural information as shown in the case of hexagonal honeycomb and kagome superlattices in surfactant lyotropic hexagonal phase intercalated with single-walled carbon nanotubes [121] and polymer nanorods [122], respectively. Figure 14 illustrates the shear-induced orientation of binary supperlattices with hexagonal honeycomb and kagome structures.…”
Section: Flow-induced Structuresmentioning
confidence: 99%